Sedimentary characteristics and evolution of the Upper Permian Wujiaping Formation in the eastern Yangtze Block - Wang, Yuanchong; Li, Hao; Mou, Chuanlong; Chen, Weiwei; Gao, Chang; Liang, Wei; Zheng, Binsong; Hou, Qian; Xia, Yu (Frontiers in Earth Science, 2024)
The Upper Permian Wujiaping (WJP) Formation in the Yangtze Block (Southern China) has great potential for shale gas exploration. However, the sedimentary characteristics and environmental evolution of the WJP Formation are poorly understood. Based on 260 hand specimen samples obtained from 18 sections and 1 borehole in the eastern Yangtze Block, petrographic observations reveal that the WJP Formation is composed of 11 rock types. Combined with analyses of geochemical compositions, the sedimentary facies belts of the WJP Formation are divided into shoreland, shallow-water shelf, deep-water shelf shoal, restricted platform, and open platform. Bauxite was developed in the shoreland at the bottom of the WJP Formation, which is attributed to the Dongwu movement. The formation of paleo-uplift exerted a significant effect on paleogeomorphology and led to a major change in the sedimentary model from the underlying stratum to the WJP Formation. During the lower WJP Formation sedimentary period, gradual transgression occurred in the eastern Yangtze Block, and the lithology was mainly composed of clastic rocks. Shoreland, shallow-water shelf, and deep-water shelf were developed northeastward in turn. In the period of the upper WJP Formation, due to durative transgression, the area of the shoreland reduced southwestward. The lithology converted from clastic rocks into carbonates, and the restricted platform and open platform were developed northeastward. A few patched shoals formed in the restricted platform.